Marketing Strategy for Integrated Islamic Elementary School Pelita Khoirul Ummah - Pratama, Septian (Universitas Islam Negeri Raden Intan Lampung, 2021)
Education is a primary need for everyone, especially the age level of children to early adulthood. Schools will be places for students to learn and develop their potential, therefore schools need to attract parents and students to choose their schools by providing adequate facilities, infrastructure and conducting marketing efforts. The Integrated Islamic Elementary School Pelita Khoirul Ummah Established in 2013 with the status of a private school under the foundation, and having its address at Jalan Langkapura, Bandar Lampung, has experienced positive growth every new academic year marked by the number of new students that continues to increase. However, opportunities and threats from external factors must be considered, in addition to trying to increase strengths and overcome weaknesses. This study aims to formulate a strategy to increase the competitive advantage of SDIT Pelita Khoirul Ummah through marketing strategy planning by analyzing its internal and external environment. This research includes applied research with a descriptive approach and qualitative method, with data sources obtained through Focus Group Discussions and interviews, then the data is analyzed using Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS), strategy analysis is carried out using the SWOT matrix. The position of the school is in quadrant 1. The strategy that must be developed is a growth-oriented strategy by trying to expand and increase market.